Effect of weld parameters on the dynamic performance of thin-walled centrifugal extractor rotating bowl. (June 2015) - Ravisankar, A; Sanapala, VS; Venugopal, S
An attempt has been made to investigate the influence of various weld parameters on the dynamic behavior of rotating bowl and thereby optimizing those parameters for the improved performance of the same. The welding input parameters play a significant role in the final distortions, which in turn cause the unbalanced mass and eccentricity, thus affecting the dynamic stability of rotor. In this regard, a synergistic approach is followed involving both finite element modeling using a coupled thermo-mechanical analysis and experimental work for estimating the induced distortion during welding. The dynamic behavior is studied comprehensively through numerical analysis by introducing the obtained distortions on the surface of the bowl after welding for different conditions such as welding speed, clamping conditions and weld sequence.